Implementasi Sistem Pengelolaan dan Perencanaan Keuangan Pribadi dengan Fitur Speech Recognition Berbasis Mobile - Yemima, Helen Ruth; Dasawaty, Elis Sondang (Jurnal Informatika dan Bisnis, 2025)
Recent technological advancements have significantly impacted various aspects of daily life, including personal financial management and planning. However, many individuals still rely on manual systems, which can be time-consuming. Manual systems require users to enter transaction data one by one, making the process tedious and lengthy. In recent years, Artificial Intelligence (AI) has become increasingly prevalent in everyday life. Speech recognition, a subfield of AI, allows machines to convert human speech into written text, facilitating human-machine interaction. Implementing speech recognition features in devices can help save time in personal financial management and planning. This research focuses on personal finance and utilizes a observation. The Extreme Programming (XP) technique is used as the software development methodology. Data measurement techniques employ formulas related to personal finance. System design begins with creating Use Case and Class Diagrams, followed by database design. The research output is a mobile application with speech recognition features for personal financial management and planning. The developed personal financial management and planning system can save time through the implementation of speech recognition features, eliminating the need for manual data entry. The system is implemented on a mobile device, providing easy access for daily personal financial management and planning.